An open‐label, randomised controlled trial on the effectiveness of the Orve + wrap® versus Forced Air Warming in restoring normothermia in the postanaesthetic care unit. Issue 7 (20th January 2020) - Smith, Neil; Abernethy, Caroline; Allgar, Victoria; Foster, Louise; Martinson, Victoria; Stones, Elizabeth
Abstract: Aims and objectives: To determine the clinical effectiveness and safety of the Orve + wrap® thermal blanket. Background: Inadvertent perioperative hypothermia is a common problem in postanaesthetic care units and can have significant effects on patients' postoperative morbidity. Despite its commercial availability, there is no clinical evidence on the effectiveness of Orve + wrap®. Design: A single centre prospective, open‐label, noninferiority randomised controlled trial. Methods: Postoperative hypothermic (35.0–35.9°C) patients who had undergone elective surgery were randomised to receive either Orve + wrap® or Forced Air Warming during their PACU stay. Patient temperatures were recorded every 10 min using zero‐heat‐flux thermometry. This study is reported using CONSORT Extension checklist for noninferiority and equivalence trials. Results: Between December 2016–October 2018, 129 patients were randomised to receive either Orve + wrap® blanket ( n  = 65, 50.3%) or Forced Air Warming ( n  = 64, 49.7%). The mean 60‐min postoperative temperature of patients receiving Orve + wrap® blanket was 36.2 and 36.3°C for the patients receiving Forced Air Warming. The predefined noninferiority margin of a mean difference in temperature of 0.3°C was not reached between the groups at 60 min. Additionally, there were no statistical differences between adverse event rates across these groups. Conclusions: In the context of this study, warming patients with the Orve + wrap® was noninferior to Forced Air Warming. There were comparable rates of associated postoperative consequences of warming (shivering, hypotension, arrhythmias or surgical site infections), between the groups. Relevance to clinical practice: The Orve + wrap® potentially provides an alternative warming method to Forced Air Warming for patients requiring short‐term postoperative warming. However, there are still a number of unknowns regarding the Orve + wrap® performance and further exploration is required.